STUDENTS' RESPONSE TO THE USE OF TELEGRAM IN ENGLISH CLASS DURING COVID-19 PANDEMIC - Lintang Kusuma; Tono Suwartono (Premise: Journal of English Education and Applied Linguistics, 2021)
In the 21st century, due to the advancement of Information and Communication Technology, the importance of English usage has increased. English teachers face considerable challenges in teaching students. Moreover, with the outbreak of COVID-19, the government issued some regulations to prevent COVID-19 transmissions at schools by changing conventional learning methods to e-learning. There are a lot of online learning applications. One popular application is Telegram Messenger. Therefore, the study aimed to determine the students' response to the use of Telegram in English class during COVID-19 pandemic and identify the obstacles they experienced when applying this application. The research respondents were the ninth-grade students at SMP Negeri 1 Kawunganten. The study was a survey using quantitative method with descriptive statistics to analyze the data. Moreover, the research employed a close-ended questionnaire. The result of students' response to the Telegram usage was 81%, resulting in the "strongly effective" category. This result indicated that Telegram was beneficial for students and very effective in English class. However, students still faced some obstacles with an average of 70%, and it indicated the level of difficulty was high. The highest problem percentage occurred in the students' concentration and motivation to study that decreased during the e-learning.